PENGARUH KINERJA KEUANGAN TERHADAP TINGKAT BAGI HASIL SIMPANAN MUDHARABAH PADA BANK MUAMALAT INDONESIA TAHUN 2008- 2010 - Nana Ernawati (2011)
The analysis to indicate F-Test conducted, that has significant level is 0.001435 the fifth of independent variable by together have correlation which are positive and significant toward deposit sharing holder level of mudharabah. But t-Test by parsial only Financing Deposit Ratio (FDR) and Net Income Margin (NIM) owning positive correlation and significant toward deposit sharing holder level of mudharabah with sig value 0.0203 and 0.0384. Return On Asset (ROA), and Biaya Operasional terhadap P